Collaboration amongst clinical nursing leadership teams: a mixed‐methods sequential explanatory study. (5th November 2014) - Lamont, Scott; Brunero, Scott; Lyons, Sarah; Foster, Karlie; Perry, Lin
Abstract : Aim: To explore intra‐professional collaboration amongst nursing leadership teams at a tertiary referral hospital in Sydney. Background: Effective working within a wide network of alliances is critical to patient outcomes. An understanding of collaboration amongst nursing leadership teams is essential within this context. Methods: A sequential explanatory mixed‐methods design was used. The Collaborative Behaviour scale was sent to 106 Nurse Unit Managers, Nurse Educators and Clinical Nurse Consultants to measure pairwise collaborative behaviours; two follow‐up focus groups with 15 participants were conducted. Data were collected between May 2012 and May 2013. A thematic analysis of focus group data provided a detailed explanation of the questionnaire findings. Results: The findings identified high collaboration between dyad groups. Two themes emerged from the thematic analysis: (1) professional role and expectations; with sub‐themes of transparency and clarity of individual roles; and intra/interpersonal aspects of role functioning; and (2) organisational infrastructure and governance. Conclusion: These leadership teams can be effective and powerful vehicles for change and are central to optimum patient outcomes. Organisational strategic planning and evaluation can benefit from understanding how to promote collaborative behaviours in these nurse leaders. Implications for nursing management: To date, little research has explored collaboration amongst nursing leadership teams. Successful collaboration may contribute to the efficient use of nursing resources; improve patient outcomes, and ultimately, nurse satisfaction and retention.